Inflammatory Myofibroblastic Tumor of the Knee in a 7-year-old Child: A Case Report - Janković, Aleksandar; Marjanović, Zoran; Bojović, Nikola; Vacić, Nikola; Božić, Dejana (Medical Word, 2025)
Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal neoplasm with intermediate malignant potential, typically occurring in children and young adults. We report a case of seven-year-old boy with a well-defined, extra-articular medial knee mass. MRI demonstrated a solid lesion with strong homogeneous enhancement without joint or bone invasion. Complete surgical excision was performed. Histopathology revealed myofibroblastic spindle-cell proliferation in a myxoid stroma with mixed inflammatory infiltrate. Immunohistochemistry showed SMA positivity and ALK negativity; molecular testing identified ROS1 rearrangement and COL1A1–PDGFRα fusion. The postoperative course was uneventful with no recurrence on follow-up. This case underscores the value of comprehensive molecular profiling in atypical IMT locations and the potential for targeted therapy in unresectable or recurrent disease.